Intestinal and Gastric Permeability in Children With Eosinophilic Esophagitis and Reflux Esophagitis. Issue 2 (February 2015) - Leung, Aldrich J.T.; Persad, Sujata; Slae, Mordechai; Abdelradi, Amr; Kluthe, Cheryl; Shirton, Leanne; Danchuk, Ronda; Persad, Rabin; Meddings, Jon; Huynh, Hien Q.
ABSTRACT: Objectives: Eosinophilic esophagitis (EoE) is an allergic and immune-mediated entity that leads to a characteristic inflammation of esophageal mucosa. Patients complain of dysphagia and reflux-like symptoms. As many as 80% of patients with EoE may also have a history of atopy, and patients with asthma and eczema have previously been shown to have increased intestinal permeability. This study was designed to assess small intestinal and gastric permeability in patients with EoE and to see whether it differed from healthy individuals and patients with reflux esophagitis (RE). Methods: Gastric and small intestinal permeability was measured using sugar probe tests containing lactulose, mannitol, and sucrose. Lactulose-to-mannitol (L/M) ratios in the patient's urine were a measure for intestinal permeability, and total sucrose was a measure for gastric permeability. Results: We analyzed samples from 23 patients with EoE, 20 RE, 14 normal upper endoscopy with gastrointestinal symptoms, and 26 healthy controls. All of the 4 groups had L/M ratios less than the upper limit of normal (<0.025). There was no statistically significant difference in gastric permeability between the 4 groups (L/M P = 0.26, sucrose P = 0.46). Conclusions: Our data suggest that an alteration in gastric and intestinal permeability does not play a role in EoE or RE pathogenesis.